2021
DOI: 10.1371/journal.pone.0253603
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel geospatial analysis of factors associated with unskilled birth attendance in Ghana

Abstract: Background Globally, about 810 women die every day due to pregnancy and its related complications. Although the death of women during pregnancy or childbirth has declined from 342 deaths to 211 deaths per 100,000 live births between 2000 and 2017, maternal mortality is still higher, particularly in sub-Saharan Africa and South Asia, where 86% of all deaths occur. Methods A secondary analysis was carried out using the 2014 Ghana Demographic and Health Survey. A sample total of 4,290 women who had a live birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…Studies found that socioeconomic conditions with geographic inequalities have significant effects on health outcomes and behaviours, such as seeking services of unskilled birth attendants in SSA countries including Chad [ 7 , 12 , 19 ]. Our geographically weighted regression (GWR) analysis showed similar findings, indicating that some regional contextual factors were associated with the prevalence of unskilled birth attendance among women in Chad.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies found that socioeconomic conditions with geographic inequalities have significant effects on health outcomes and behaviours, such as seeking services of unskilled birth attendants in SSA countries including Chad [ 7 , 12 , 19 ]. Our geographically weighted regression (GWR) analysis showed similar findings, indicating that some regional contextual factors were associated with the prevalence of unskilled birth attendance among women in Chad.…”
Section: Discussionmentioning
confidence: 99%
“…Women with no formal education in sub-regions or departments of the northern and eastern parts of Chad were about 6.8% more likely to experience or seek the services of unskilled birth attendants. A possible reason is that women with no formal education in those areas may have limited knowledge about the possible consequences of unskilled birth attendance, or where to seek services of skilled birth attendants [ 7 , 12 ]. Occupational or employment disparities also play a significant role in the prevalence of unskilled birth attendance among women in Chad.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GWR is a local model that estimates the different responses of the dependent variable on independent variables based on locational effects [22]. This explains the spatial predictive power of the signi cant factors explaining the occurrence of the noncompliance of ANC in Ghana.…”
Section: Spatial Distribution Of Anc Noncompliancementioning
confidence: 99%